Cardiac Septal Defects in Children: Hemodynamics, Clinical Manifestations and Detection - Ria Nova; Sukman Tulus Putra; Siti Nurmaini; Radiyati Umi Partan (HM Publisher, 2021)
Cardiac septal defect in children is one of the congenital heart defects characterized by atrial septal defects (ASD), ventricular septal defects (VSD) and defects in both atrial and ventricular septum (AVSD). The hemodynamic changes that occur are caused by a left to the right shunt. Differences in location, size of the defect and pulmonary vascular resistance make hemodynamic differences and clinical manifestations between the three types of cardiac septal defects. Detection of cardiac septal defects can be done by clinical examination by listening to the characteristic heart sounds and murmurs for each defect. However, clinical examination alone is often still difficult to determine the type of cardiac septal defect so that several supporting examinations such as photothorax, ECG, echocardiogram and cardiac catheterization need to be done to help establish the diagnosis.